Understanding the self and others : explorations in intersubjectivity and interobjectivity - Sammut, Gordon; Daanen, Paul.; Moghaddam, Fathali M. (New York : Routledge, 2013)
'How do we, as human beings, come to understand ourselves and others around us? This question couldn't be more timely or pertinent to the issues facing humanity today. At the heart of most of our world's most troubling political and social problems lies a divergence in perspectives between nations and/or cultural groups. For example, how should we characterize the seemingly intractable divide between Indians and Pakistanis? What lies at the heart of the constant misunderstanding between Israelis and Palestinians? How has the political divide in the United States taken on such polemic divisions? How are we to make sense of the baffling resistance certain groups of people in many nations have to the overwhelming evidence of global climate change? In essence, the divergences in all of these perspectives are related to fundamentally different ways in which groups value their existence and construct a meaningful picture of who they are in relation to others. By drawing on multidisciplinary approaches to social psychological phenomena illustrated in these examples, this book draws together a number of cutting edge researchers and practitioners in psychology and related fields. The discussions in this book both review some of the most significant debates concerning how different groups come to share meanings, and radically advance this discussion in impactful new directions.'--
'How do we, as human beings, come to understand ourselves and others around us? This question could not be more timely or pertinent to the issues facing humankind today. At the heart of many of our world's most troubling political and social problems lies a divergence, and sometimes a sharp contradiction, in perspectives between nations and cultural groups. To find potential solutions to these seemingly intractable divides, we must come to understand what both facilitates and hinders a meaningful exchange of fundamental ideas and beliefs between different cultural groups. The discussions in this book aim to provide a better understanding of how we come to know ourselves and others. Bringing together a number of cutting edge researchers and practitioners in psychology and related fields, this diverse collection of thirteen papers draws on psychology, sociology, philosophy, linguistics, communications, and anthropology to explore how human beings effectively come to understand and interact with others. This volume is organised in three main sections to explore some of the key conceptual issues, discuss the cognitive processes involved in intersubjectivity and interobjectivity, and examine human relations at the level of collective processes. Understanding the Self and Others will appeal to students and scholars of sociology, developmental psychology, philosophy, communication studies, anthropology, identity studies, social and cultural theory, and linguistics'--
Includes bibliographical references and index.
Keywords: Social interaction; National characteristics; Social groups